Composing the Party Line Music and Politics in Early Cold War Poland and East Germany - Tompkins, David G. (Purdue University Press, 2013)
Examines the exercise of power in the Stalinist music world as well as the ways in which composers and ordinary people responded to it. A comparative inquiry into the relationship between music and politics in the German Democratic Republic and Poland from the aftermath of World War II through Stalin's death in 1953, concluding with the slow process of de-Stalinization in the mid-to-late 1990s. This book examines the exercise of power in the Stalinist music world as well as the ways in which composers and ordinary people responded to it. It presents a comparative inquiry into the relationship between music and politics in the German Democratic Republic and Poland from the aftermath of World War II through Stalin's death in 1953, concluding with the slow process of de-Stalinization in the mid- to late-1950s.